Statistical Modeling of Antenna: Urban Equipment Interactions for LTE Access Points - Xin Zeng; Alain Sibille (International Journal of Antennas and Propagation)
The latest standards for wireless networks such as LTE are essentially based on small cells in order to achieve a large network capacity. This applies for antennas to be deployed at street level or even within buildings. However, antennas are commonly designed, simulated, and measured in ideal conditions, which is not the real situation for most applications where antennas are often deployed in proximity to objects acting as disturbers. In this paper, three conventional wireless access point scenarios (antenna-wall, antenna-shelter, and antenna lamppost) are investigated for directional or omnidirectional antennas. The paper first addresses the definition of three performance indicators for such scenarios and secondly uses such parameters towards the statistical analysis of the interactions between the wall and the antennas.